Human Keratinocytes Express Cellular Prion-Related Protein in Vitro and during Inflammatory Skin Diseases - Pammer, Johannes (American Society for Investigative Pathology, 1998)
Prion diseases are transmissible spongiform encephalopathies of humans and animals characterized by the accumulation of a proteinase-resistant isoform of the cellular prion-related protein (PrP(c)) within the central nervous system. In the present report we demonstrate for the first time the presence of PrP(c) on squamous epithelia of normal and diseased human skin and show that inflammatory cytokines regulate PrP(c) expression in cultured human keratinocytes (KCs). By immunohistochemistry, only little expression of PrP(c), which was mainly confined to KCs, was detected in normal skin. In contrast, in inflammatory skin diseases including psoriasis and contact dermatitis, PrP(c) was strongly present on both KCs and infiltrating mononuclear cells. Strong PrP(c) expression was also observed in squamous cell carcinomas and viral warts whereas basal cell carcinomas were mostly negative. In mucous membranes of the upper digestive tract and the genital region, distinct PrP(c) expression by basal squamous epithelial cells was a constant feature. In tissue culture, primary KCs constitutively expressed PrP(c) mRNA and protein. Exposure of these cells to transforming growth factor (TGF)-α or interferon (IFN)-γ led to an increase of PrP(c) protein expression. The presence of PrP(c) on epithelial cells of skin and mucous membranes suggests that these cells represent possible first targets for peripheral infection with prions.